Insights Into Oral Manifestations As Diagnostic Indicators Of Viral Infections : A Literature Review - Sovira, Gita Dwi Jiwanda; Achmad Syawqie (Jurnal EduHealth, 2024)
Background: Infectious diseases, particularly viral infections, represent a major global health concern, with significant implications for oral health. Despite their clinical relevance, oral manifestations of viral infections are often underdiagnosed due to their complex and varied presentations. Early recognition of these manifestations can aid in timely diagnosis and management, improving overall patient outcomes. Objective: This study aims to systematically review the oral manifestations associated with viral infections to provide a comprehensive reference for healthcare professionals in diagnosing and managing such conditions. Methods: A systematic review was conducted using five databases, including PubMed and Scopus, to identify relevant studies published between 2014 and 2024. Keywords such as "oral manifestation" and "viral infection" were used. Eligible studies were selected based on predefined inclusion and exclusion criteria, focusing on articles in English with clinical relevance to oral health. Data were extracted independently by multiple authors and analyzed to identify patterns and significant findings regarding oral manifestations of viral infections. Results: The review identified 133 articles, with 24 studies meeting the inclusion criteria. Key findings revealed that human herpesviruses, including HSV-1, HSV-2, VZV, EBV, CMV, HHV-6, HHV-7, and HHV-8, frequently present with distinct oral lesions. These lesions range from vesicles and ulcers to gingival overgrowth and vascular tumors. The study highlights the diagnostic importance of oral findings, particularly in immunocompromised patients. Conclusion: Oral manifestations are critical diagnostic indicators of viral infections and provide an opportunity for early disease recognition. A thorough understanding of these manifestations can enhance clinical diagnosis, reduce healthcare costs, and improve patient outcomes. Future research should focus on developing diagnostic algorithms incorporating oral and systemic findings for better clinical utility.